2021
DOI: 10.33590/emjurol/21-00094
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota and Kidney Transplantation: Influence on the Graft

Abstract: The gut microbial community may be associated with complications after kidney transplantation. The indigenous microbiota has a significant and protective function that influences the transplant recipient response. Genetic or environmental factors may modify the indigenous microbiota and pathobionts appear. In this condition, several disturbances of the kidney graft may be observed. These include acute rejection, infection, diarrhoea, disturbance in the induction of tolerance, and modification of immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Checkpoint inhibitor therapy is a type of cancer immunotherapy that targets and binds to key immune checkpoint proteins, thereby blocking T-cell inhibitory responses, restoring immune function, and consequently directing the immune system against malignant cells ( 199 201 ). The authors reported an association between higher microbial diversity and optimistic treatment outcomes, a finding in agreement with observations made in studies investigating allograft maintenance outcomes in the context of different human microbiotas ( 141 , 143 , 202 204 ). The metagenomic implications of different chemotherapeutic as well as dietary interventions in renal cell carcinoma patients is an area of active investigation.…”
Section: Renal Transplantationsupporting
confidence: 87%
See 2 more Smart Citations
“…Checkpoint inhibitor therapy is a type of cancer immunotherapy that targets and binds to key immune checkpoint proteins, thereby blocking T-cell inhibitory responses, restoring immune function, and consequently directing the immune system against malignant cells ( 199 201 ). The authors reported an association between higher microbial diversity and optimistic treatment outcomes, a finding in agreement with observations made in studies investigating allograft maintenance outcomes in the context of different human microbiotas ( 141 , 143 , 202 204 ). The metagenomic implications of different chemotherapeutic as well as dietary interventions in renal cell carcinoma patients is an area of active investigation.…”
Section: Renal Transplantationsupporting
confidence: 87%
“…Over the past several years, there has been a prominent increase in interest surrounding the various human microbiotas and their respective roles in kidney allograft maintenance as well as rejection ( 141 ). Furthermore, in addition to the five types of non-invasive chronic kidney transplant rejection biomarker technologies (transcriptomic, cellular, epigenetic, proteomic, and metabolomic) currently utilized, the human microbiota may also become an insightful biomarker to predict allograft outcomes, therapy responsiveness, and patient-specific susceptibilities/sensitivities to specific drugs such as antimicrobials and immunosuppressants ( 130 , 139 , 142 , 143 ).…”
Section: Renal Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…FMT is an established therapy for recurrent CDI, with a treatment efficacy above 85% [42]. Moreover, accumulating studies have shown the benefit of FMT for several diseases associated with dysregulated gut microbiota, including autism, cancer, and type 2 diabetes [7,[43][44][45][46]. Although studies using FMT to prevent or treat CKD are still limited, preliminary evidence of the efficacy of FMT indicates that the application of FMT may offer a promising alternative for the treatment of CKD.…”
Section: Introductionmentioning
confidence: 99%